2003
DOI: 10.1590/s1517-74912003000100018
|View full text |Cite
|
Sign up to set email alerts
|

Homeobox genes: a molecular link between development and cancer

Abstract: Homeobox genes are regulatory genes encoding nuclear proteins that act as transcription factors, regulating aspects of morphogenesis and cell differentiation during normal embryonic development of several animals. Vertebrate homeobox genes can be divided in two subfamilies: clustered, or HOX genes, and nonclustered, or divergent, homeobox genes. During the last decades, several homeobox genes, clustered and nonclustered ones, were identified in normal tissue, in malignant cells, and in different diseases and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0
16

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(65 citation statements)
references
References 35 publications
1
48
0
16
Order By: Relevance
“…The intricate relationship between normal cell development and carcinogenesis has long been under scrutiny (51). As they are master regulators of embryogenesis, the deregulation of homeobox genes has profound effects on the cellular phenotype and may lead to tissue neoplasia (55,57).…”
Section: Discussionmentioning
confidence: 99%
“…The intricate relationship between normal cell development and carcinogenesis has long been under scrutiny (51). As they are master regulators of embryogenesis, the deregulation of homeobox genes has profound effects on the cellular phenotype and may lead to tissue neoplasia (55,57).…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative analysis showed the expression level of HOXA7 was significantly higher in the granulosa tumor cell line, KGN, compared to primary hGCs and SVOG cells. It has been reported that many cancers, including leukemia, colon, skin, prostate, breast and ovarian cancers, have shown alterations in the expression patterns of HOX genes [30,32]. The overexpression of HOX genes has been widely associated with a variety of ovarian carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…The absent or aberrant expression of tissue-specific HOX genes has been implicated in cancer development [4]. Changes in HOX gene expression have been documented in small-cell lung cancer, breast cancer, prostate cancer, colorectal cancer, esophageal cancer, and kidney cancer [5][6][7]. Despite the observance of these changes little is known about the regulation of the HOX genes in adult tissues and how the genes become deregulated in cancerous tissues.…”
Section: Introductionmentioning
confidence: 99%